Seeking support or avoiding it? A qualitative study of professional psychological help perceptions among university students in Honduras - Rivera, Estyben; Barahona-Aguilar, César; Cuevas, Gamariela; Orellana-Moreno, Flor; Corrales, Irma; Mejía-Sánchez, Raquel; Paz-Maldonado, Eddy; Landa-Blanco, Miguel (Frontiers in Psychology, 2025)
University students face significant mental health challenges exacerbated by barriers such as stigma, financial constraints, and limited services. This study examined barriers to seeking psychological help among 23 students from the National Autonomous University of Honduras (UNAH). Participants were recruited through social media, snowball sampling, and campus visits. Using semi-structured interviews, the research explored attitudes, barriers, and perceptions regarding professional psychological help. Interview guides were expert-validated and pilot-tested. Thematic analysis, conducted from a constructivist perspective, identified four themes: motivators, psychotherapy sources, barriers, and facilitators. Findings revealed that while stigma and financial constraints hinder help-seeking, motivators like personal growth and social influences encourage it. The study highlighted the need for accessible mental health services in university settings to address academic and social pressures. Strengthening these services is essential to fostering a supportive environment that promotes student well-being and psychological resilience.